Gamma Delta T Cells and Their Involvement in COVID-19 Virus Infections - von Massow, Georg; Oh, Steve; Lam, Alan; Gustafsson, Kenth (Frontiers in Immunology, 2021)
The global outbreak of the SARS-Cov-2 virus in 2020 has killed millions of people worldwide and forced large parts of the world into lockdowns. While multiple vaccine programs are starting to immunize the global population, there is no direct cure for COVID-19, the disease caused by the SARS-Cov-2 infection. A common symptom in patients is a decrease in T cells, called lymphopenia. It is as yet unclear what the exact role of T cells are in the immune response to COVID-19. The research so far has mainly focused on the involvement of classical ⍺β T cells. However, another subset of T cells called 𝛾𝛿 T cells could have an important role to play. As part of the innate immune system, 𝛾𝛿 T cells respond to inflammation and stressed or infected cells. The 𝛾𝛿 T cell subset appears to be particularly affected by lymphopenia in COVID-19 patients and commonly express activation and exhaustion markers. Particularly in children, this subset of T cells seems to be most affected. This is interesting and relevant because 𝛾𝛿 T cells are more prominent and active in early life. Their specific involvement in this group of patients could indicate a significant role for 𝛾𝛿 T cells in this disease. Furthermore, they seem to be involved in other viral infections and were able to kill SARS infected cells in vitro. 𝛾𝛿 T cells are already used for medical purposes in oncology and have potential in cancer therapy. As 𝛾𝛿 T cells are not necessarily able to distinguish between a transformed and a virally infected cell it could therefore be of great interest to investigate further the relationship between COVID-19 and 𝛾𝛿 T cells.